Accelerated Technological Progress - An Explanation for Wage Dispersion and a Possible Solution to the Productivity Paradox - Oliver Nikutowski (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2007)
Due to scarcity considerations an increase in the supply of college graduates should reduce the premium for this kind of qualification. Therefore it seems quite contradictory that a tremendous educational expansion in the USA is accompanied by rising wage dispersion (overall and between educational groups). A second seemingly paradox development, which occured simultaneously, is the reduction of the total factor productivity during the emergence of the computerage - the so called productivity paradox. This contribution offers a simple unified solution to both of these puzzles and explains the educational expansion by assuming accelerated technological progress: An increase in the speed of technological progress raises the economic value of prospective periods and therefore works in favor of timeconsuming higher qualifications. The resulting educational expansion firstly goes along with a composition effect which leads to wage dispersion. Secondly the additional absence from the labor market of some more able individuals, due to the longer qualification, as well as an increasing share of individuals who choose a less productive qualification may lead to a transitory slowdown of the productivity growth rate.
urn:nbn:de:bvb:19-epub-1925-8
Keywords: J21; J22; J23; J24; J31; J82; O15; O33; O47; 330; Wage Dispersion; Productivity Paradox; Inequality; Distribution; Technological Progress; Technological Change; SBTC; Educational Expansion; Total Factor Productivity; Educational Signaling; Real Wage Losses; Lohnspreizung; Produktivitätsparadox; Ungleichheit; Verteilung; Technologischer Fortschritt; Technologischer Wandel; SBTC; Bildungsexpansion; Totale Faktorproduktivität; Bildungssignale; reale Lohnsenkung; Technischer Fortschritt; Bildungsniveau; Einkommensverteilung; Theorie; USA